2021
DOI: 10.1007/s10096-021-04320-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of mouthwash sampling in SARS-CoV-2 diagnosis

Abstract: Background The current practice of COVID-19 diagnosis worldwide is the use of oro-nasopharyngeal (ONP) swabs. Our study aim was to explore mouthwash (MW) as an alternative diagnostic method, in light of the disadvantages of ONP swabs. Methods COVID-19 outpatients molecular-confirmed by ONP swab were repeatedly examined with ONP swab and MW with normal saline (0.9%). Other types of fluids were compared to normal saline. The Cq values obtained with each method were compar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
(24 reference statements)
1
12
0
Order By: Relevance
“…Cost and time were also accounted for [2,38]. Secondly, to prevent false negatives, the relatively conserved N-gene among sarbecoviruses was selected over S, E, or ORF -n as detection targets [1,3,4,27,38,39]. As SARS-CoV-2 global genomic databases increased (Mexican sequences rose from 28 to 720 by February 2021), primer/probe specificity was successfully confirmed three times in this research with 209 sequences, including virus Alpha strain and related respiratory virus.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Cost and time were also accounted for [2,38]. Secondly, to prevent false negatives, the relatively conserved N-gene among sarbecoviruses was selected over S, E, or ORF -n as detection targets [1,3,4,27,38,39]. As SARS-CoV-2 global genomic databases increased (Mexican sequences rose from 28 to 720 by February 2021), primer/probe specificity was successfully confirmed three times in this research with 209 sequences, including virus Alpha strain and related respiratory virus.…”
Section: Discussionmentioning
confidence: 81%
“…However, our MWS procedure is the first that demonstrates oral fluid efficacy for early, low virus titer detection (≥3.6 VCN/reaction, 37.6 Ct). Two reported mouthwash procedures, conducted with suspected [26] or positive cases [27], had contrasting results being effective only in the latter; perhaps due to limited virus concentration in the 10 mL of sterile water or normal saline used for washing. In this work, MWS was applied in heterogeneous ambulatory cohorts, including asymptomatic and mild-symptom suspected COVID-19 cases without preceding testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these 19 study populations, seven assessed the diagnostic performance of gargle in populations with suspected infection [ 28 , 49 , 50 , 54 , 55 , 57 , 59 ], and 12 assessed the use of gargle for monitoring viral shedding in populations already confirmed to have SARS-CoV-2 infections, either as hospital inpatients or after being discharged ( table 1 ) [ 29 , 35 , 36 , 46 48 , 51 53 , 56 , 58 , 59 ]. Regarding the study location, there were five studies from Canada [ 28 , 47 , 50 , 52 , 57 ], six from Germany [ 36 , 48 , 49 , 51 , 54 , 56 ] and with the rest (seven) from Finland [ 29 ], Turkey [ 55 ], China [ 46 ], Korea [ 58 ], Indonesia [ 59 ], Israel [ 53 ] and India [ 35 ]. These studies spanned from 23 March 2020 to 19 July 2021, covering the period of different prevailing SARS-CoV-2 variants, from the ancestral strain, alpha variant, to its delta variant.…”
Section: Resultsmentioning
confidence: 99%
“…23 Previous studies indicated that sample collection can be feasibly improved to increase the sensitivity of saliva for PCR by using a saliva swab and supervised self-saliva collection, 26 self-collected deep throat saliva, 24,25,27 or rinse-gargle saliva. 28,29 Additional improvements of the LAMP method include the selection of alternative gene targets, such as the N gene or simultaneously use of multiple genes as targets such as E, N, and Orf, [30][31][32][33] as well as optimized sample processing to minimize interference from the specimen pH, especially for FS, with the colorimetric method. Other enhancements could include the use of a thermal cycle machine, a digital or fluorescence reader for amplification detection, and insulated containers to stabilize the incubation temperature for the LAMP reaction.…”
Section: Discussionmentioning
confidence: 99%